John’s Farewell Discourse under the Shadow of Mark - Bowes, William (The Biblical Annals, 2026)
The lengthy discourses of John’s Gospel are a feature of the Evangelist’s writing which has contributed to the idea that he wrote independently of other Gospels. The absence of such discourses in the Synoptics might suggest that John’s discourses are idiosyncratic vehicles for theologizing, wherein Jesus’ speech mirrors Johannine idiom. In this article, I re-examine Jesus’ farewell discourse in John 13–17 in light of the view that John is dependent on Mark’s Gospel. Although John 13–17 is not often considered a connection between these Gospels, I argue that John built this material from Mark 12–14, seeking to improve and expand Mark in a competitive literary marketplace and to persuade his readers to view Jesus and themselves in a particularly Johannine way. John’s compositional practices in his farewell discourse material be compared with two Jewish texts (Chronicles and Jubilees) which reinterpret earlier source material to create farewell discourses.